Mental Health Problems and Effective Leadership in Educational Institution in Ogun State, Nigeria - Fejoh, Johnson; Onanuga, Paul Adekunle (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Mental Health Problems and Effective Leadership in Educational Institution in Ogun State, Nigeria Abstract This study investigated the relationship between mental health problems and effective leadership in educational institutions in Ogun State, Nigeria. It examined the impact of acute stress disorder (ASD), burnout and depressive episodes on leadership effectiveness among educational administrators. A descriptive survey research design was employed, with a sample of 385 participants selected through stratified random sampling. Standardized scales, including the Acute Stress Disorder Questionnaire, Maslach Burnout Inventory, Beck Depression Inventory-II and Leadership Effectiveness Scale, were used to collect data. Simple linear regression analysis revealed significant negative impacts of ASD (β = -.259, t = 12.217, p < .0005), burnout (β = -.211, t = 10.903, p < .0005) and depressive episodes (β = -.196, t = 9.278, p < .0005) on leadership effectiveness. The findings highlighted the need for institutions to prioritize mental health support for educational administrators to mitigate the negative impacts of mental health problems on leadership effectiveness. The study recommended investing in leadership development programmes that address mental health and wellness, and taking proactive measures to support administrators' mental health.